2007
DOI: 10.1603/0022-0493(2007)100[695:eoaawa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an African Weaver Ant, <I>Oecophylla longinoda</I>, in Controlling Mango Fruit Flies (Diptera: Tephritidae) in Benin

Abstract: Six mango, Mangifera indica L., plantations around Parakou, northern Benin, were sampled at 2-wk intervals for fruit fly damage from early April to late May in 2005. Mean damage ranged from 1 to 24% with a weaver ant, Oecophylla longinoda (Latreille), being either abundant or absent. The fruit fly complex is made up of Ceratitis spp. and Bactrocera invadens Drew et al., a new invasive species in West Africa. In 2006, Ceratitis spp. peaked twice in the late dry season in early April and early May, whereas B. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(13 citation statements)
references
References 1 publication
2
11
0
Order By: Relevance
“…Among the beneficial insect species which may regulate insect pest populations, we observed a diversity of ant species, some of which have already been reported by many authors in Benin, Ghana, Nigeria, and Tanzania, on cashew trees and other plants ( Van Mele et al. 2007 , Dwomoh et al.…”
Section: Discussionsupporting
confidence: 64%
“…Among the beneficial insect species which may regulate insect pest populations, we observed a diversity of ant species, some of which have already been reported by many authors in Benin, Ghana, Nigeria, and Tanzania, on cashew trees and other plants ( Van Mele et al. 2007 , Dwomoh et al.…”
Section: Discussionsupporting
confidence: 64%
“…In particular studies, the presence of ants significantly reduced pest densities of leaf-footed bugs (Coreidae; Peng et al, 1999;Dwomoh et al, 2009), mirid bugs (Miridae; Peng et al, 1999;Ayenor et al, 2007;Dwomoh et al, 2009;Forbes and Northfield, 2017a), stink bugs (Pentatomidae; Peng et al, 1999;Hosetti and Rudresh, 2012) and fruit flies (Tephritidae;Van Mele et al, 2007;Adandonon et al, 2009;Migani et al, 2017) (Figure 4A). Particular studies reported reduced pest damage from weevils (Curculionidae; (Peng and Christian, 2007;Peng et al, 2014;Abdulla et al, 2016)), fruit flies (Peng and Christian, 2006;Diame et al, 2015;Abdulla et al, 2017), and mirid bugs (Peng et al, 1995(Peng et al, , 2014Peng and Christian, 2008;Olotu et al, 2013;Abdulla et al, 2015) in the presence of ants ( Figure 4C).…”
Section: Resultsmentioning
confidence: 93%
“…Ant treatments had significantly fewer pests and less pest damage than treatments without ants. Outliers are shown as white dots, while the solid black line indicates the median and the box shows the distribution of the dataset compiled from 25 studies (Peng et al, 1995(Peng et al, , 1999(Peng et al, , 2011(Peng et al, , 2012(Peng et al, , 2013(Peng et al, , 2014Sporleder and Rapp, 1998;Peng and Christian, 2004, 2005b, 2008Ayenor et al, 2007;Van Mele et al, 2007;Adandonon et al, 2009;Dwomoh et al, 2009;Hosetti and Rudresh, 2012;Olotu et al, 2013;Pierre and Idris, 2013;Abdulla et al, 2015Abdulla et al, , 2016Abdulla et al, , 2017Anato et al, 2015;Diame et al, 2015;Forbes and Northfield, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weaver ants ( Oecophylla spp.) are utilized for biological control of insect pests in a number of tropical tree crops (Peng et al 2004 , 2010 ; Van Mele et al 2007 ) and are in this way known to improve fruit quality (Sinzogan et al 2008 ; Peng et al 2004 ). They are therefore increasingly being utilized as a substitute for synthetic chemical pesticides (Dwomoh et al 2009 ; Offenberg et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%